Utilizacion de la tierra e importancia de la yuca en la finca DRI en los Departamentos de Atlantico, Bolivar, Cordoba y Sucre - Janssen, W. (International Center for Tropical Agriculture, 1984)
The results of a survey conducted in 1983 among 416 farmers participating in the integrated rural development project (DRI, Colombia) in Atlantico (60), Bolivar (66), Cordoba (156), and Sucre (134), on land use and importance of cassava within the farming system, are presented. Except for Bolivar, where cassava and yam plantings decreased, increased land use attributable to increased credit availability was observed. In general, 1.7 ha cassava was planted per farm in 1982-83, mainly in association with yam, maize, and plantains; 55 percent of the land planted included cassava. On the other hand, cassava monocrops are not common and represent an option only when not enough money is available to plant cassava in association. Over 70 percent of the farmers make arrangements with middlemen prior to harvest and more than 50 percent of the cassava is for human consumption. The increased production of these traditional crops has caused marketing problems; in the case of cassava, drying projects have tried to solve them. (CIAT)